Integrated management of white rot and root rot – wilt disease complex of pea - and A. SINGH, A.S. KAPOOR*, Y.S. PAUL (Indian Phytopathology, 2006)
The incidence of root rot-wilt disease complex and white rot were least where ever pea-kuth or pea-onion rotation was followed in zone IV whereas, in zone II the rice / maize- pea rotation was found effective compared to French bean – pea rotation. Host resistance studies revealed 4 lines resistant to root rot / wilt complex. Soil application of Trichoderma koningii (RMA-8) @ 2.5 kg/65 kg of FYM/ha reduced the pea root rot/ wilt disease complex whereas Trichoderma harzianum (SMA-4) was more effective against white rot. Neem based biopesticide Wanis @ 0.1 was most effective against Fusarium oxysporum f. sp. pisi, and F. solani f.sp. pisi and Sclerotinia sclerotiorum. Among the different integration levels, amendment with Lantana camara (10t/ha) + bioagent Tricoguard @ 2.5kg/ 62 kg FYM/ ha + spray with carbendazim at pre flowering stage was most effective in managing the root rot-wilt complex disease in pea.